Oophoropexy for Recurrent Ovarian Torsion. (6th February 2018) - Hartley, Jennifer; Akhtar, Muhammad; Edi-Osagie, Edmond
Abstract : A 31-year-old nulliparous patient presents with a three-day history of right sided colicky abdominal pain and associated nausea. This patient has previously presented twice with right sided ovarian torsion with the background of polycystic ovaries in the last two consecutive years. Blood tests were normal. Due to previous history, there was a high index of clinical suspicion that this may be a further torsion. Therefore, the patient was taken to theatre for a diagnostic laparoscopy and a further right sided ovarian torsion was noted. At this time, oophoropexy was performed to the uterosacral ligament to prevent further torsion in order to preserve the patients' fertility. In this article, we detail this case and also provide a discussion of ovarian torsion including risk factors, presentation, and current thoughts on management.